Drak Is Required for Actomyosin Organization During Drosophila Cellularization - Chougule, Ashish B. (G3 (Bethesda), 2016)
The generation of force by actomyosin contraction is critical for a variety of cellular and developmental processes. Nonmuscle myosin II is the motor that drives actomyosin contraction, and its activity is largely regulated by phosphorylation of the myosin regulatory light chain. During the formation of the Drosophila cellular blastoderm, actomyosin contraction drives constriction of microfilament rings, modified cytokinesis rings. Here, we find that Drak is necessary for most of the phosphorylation of the myosin regulatory light chain during cellularization. We show that Drak is required for organization of myosin II within the microfilament rings. Proper actomyosin contraction of the microfilament rings during cellularization also requires Drak activity. Constitutive activation of myosin regulatory light chain bypasses the requirement for Drak, suggesting that actomyosin organization and contraction are mediated through Drak’s regulation of myosin activity. Drak is also involved in the maintenance of furrow canal structure and lateral plasma membrane integrity during cellularization. Together, our observations suggest that Drak is the primary regulator of actomyosin dynamics during cellularization.